توظيف التنمية البشرية في خدمة الدعوة إلى الله -دراسة تحليلية لبرنامج الطاقة البشرية للدكتور إبراهيم الفقي*رحمه الله*- - تريكي, حفيظة (University of Eloued جامعة الوادي, 2018)
"هدفت الدراسة إلى معرفة كيف وُظِفَت التنمية البشرية في خدمة الدعوة إلى الله، وذلك من خلال تحليل محتوى برنامج الطاقة البشرية مضموناً من خلال الإجابة على سؤال(ماذا قيل؟) وشكلاً بالإجابة على سؤال(كيف قيل؟). هذا وقد اعتمدت الدراسة على المنهج الوصفي، وأداة تحليل المضمون لجمع البيانات، بحيث بلغت فئات التحليل(58) فئة، وتحقيقا لهدف الدراسة تم اختيار جميع حلقات البرنامج تكونت من(07) حلقات من برنامج الطاقة البشرية، جرى تحليلها وفقاً لإستمارة تحليل المضمون التي تم تحكيمها من قبل عدة أساتذة مختصين في الدراسات الإعلامية. توصلت الدراسة إلى أن التنمية البشرية لها دورها الفعّال في خدمة الدعوة إلى الله وذلك بتوظيف التفكير الإيجابي والإتصال اللذان يركزان بشكل كبير على جعل التنمية البشرية أحد أهم مقتضيات الدعوة إلى الله حيث على الداعي أن يكون صاحب رؤية في هذا المجال. " "The study aimed at knowing how human development was used in the service of the Preaching (to Allah) by analyzing the content of the human energy program. It is guaranteed by answering the question(what was said?) And how to answer the question (how was it said?). The study was based on the descriptive approach and the content analysis tool to collect the data, so that the categories of analysis reached(58) categories. To achieve the objective of study, all the workshops were chosen from(07) episodes of the human energy program, Arbitrated by specialized professors. The study found that human development has an effective role in serving the Preaching (to Allah) by employing positive thinking and communication, which focus greatly on making human development one of the most important requirements of the Preaching (to Allah), where the Preacher should possess a vision in this field. "
مذكرة ماسترتخصص دعوة و اعلام
Keywords: وظيف -التنمية البشرية - خدمة الدعوة إلى الله; human development- the service of the Preaching (to Allah)